Reproductive traits of the European hake, Merluccius merluccius (L. 1758), in the Adriatic Sea - Zorica, Barbara (Array, 2021)
Within this paper, reproduction traits of the Adriatic population European hake, Merluccius merluccius (Linnaeus, 1758), were investigated. Specimens of the target species were monthly collected (N=1173) during 2019 along the eastern Adriatic Sea with commercial bottom trawlers. Overall, European hake total body length varied between 15.5 and 49.5 cm (mean±SD=27.5±5.0 cm) and domination of females was noted in larger length classes (TL>31.0 cm). The sexual ratio of all specimens was m/f=0.64; male prevalence was established over the year, except during the spawning peaks (December, June) when the sex ratio was in favour of the females. According to European hake"s maturity stages, gonad weights, gonadosomatic indexes and histological analysis of the gonad tissues, this species in Adriatic spawn twice in one year; the spawning period was from December to February, while second smaller signs of spawning were observed at the beginning of the summer, in June. 50% of the European hake male and female specimens sexually matured at 20.7 cm and 22.4 cm of total length, respectively.